The application of SUDEP in forensic diagnosis: a mini review - Sun, Daming; Wang, Qiang (Frontiers in Neurology, 2023)
In the epilepsy population, the risk of sudden death from epilepsy is rare but is ~24 times greater than the risk of sudden death from other causes. Sudden unexpected death in epilepsy (SUDEP) has been widely recognized in clinical studies. Despite its significance as a cause of death, SUDEP is rarely used in forensic practice. This review focuses on the forensic characteristics of SUDEP, analyzed the reasons for its underuse in forensic practice, and illustrated the prospect of establishing uniform diagnostic criteria for sudden unexpected death in epilepsy and molecular anatomy in aiding forensic diagnosis.